ANALISIS USAHA PETERNAKAN AYAM BROILER POLA KEMITRAAN DI KOTA PEKANBARU - Cepriadi dan; Susy Adwina (Jurnal Peternakan, 2007)
This research aim to know companies patnership implementation toward broii~r chicken keeper; also to know the income differences at different company scales in Pekanbara city. This research was done during six month, from Juni to November 2003. Result of research of show that in Pekanbaru there are ~ partner pattel;'n which have been recognized in general, that is Ramah Tamah Indah (RTI), Makmur Jaya, Confred; and of Pokphand. Research methodology of this research was case study and u~ing propotiona,lsampli:ng techniqUe towanl 36 broiler chicken keepers as the sample. The sample were devided into three categories, sc~e1< 5.000 chic;ken, sca1ell (5.00010.000) chicken and scale 1lI > 10.000 chicken. The results show the patnership modeISthat could not be reciIized are letter of agreement, land ownership letter of chicken keepers, sapronak of the companies, companies technical assistance, devident calculating system and devident taking after harvest, minimal production 5.000 chicken, the continuity of sapronak delivery, sapronak prices, harvest schedule and the price of selling ..